Gastrointestinal Bleeding due to Pancreatic Disease-Related Portal Hypertension - Zheng, Kexin; Guo, Xiaozhong; Feng, Ji; Bai, Zhaohui; Shao, Xiaodong; Yi, Fangfang; Zhang, Yongguo; Zhang, Rui; Liu, Han; Romeiro, Fernando Gomes [UNESP]; Qi, Xingshun (Hindawi, 2020)
Background and Aims. Left-sided portal hypertension (LSPH) is a rare type of portal hypertension, which occurs due to obstruction, stenosis, or thrombosis within the splenic vein. Pancreatic diseases are the most common etiology of LSPH. This study is aimed at reporting our experiences and discussing the presentation, management, and prognosis of LSPH secondary to pancreatic diseases. Patients and Methods. We retrospectively reviewed five patients who were diagnosed with LSPH secondary to pancreatic diseases at our department. We collected the demographic information, history, comorbidities, clinical presentations, laboratory tests, esophagogastroduodenoscopy (EGD), images, and outcome data. Results. Three elderly patients (>60 years old) were diagnosed with pancreatic cancer, of whom one underwent laparoscopic radical distal pancreatectomy and splenectomy, one received chemotherapy, and another one chose conservative management due to multiple systemic metastases. Two younger patients (<40 years old) were diagnosed with acute recurrent pancreatitis and chronic pancreatitis. Four of these five included patients presented with hematemesis and/or melena at our admission. All patients had gastric varices, and one of them also had esophageal varices. One elderly patient with metastatic pancreatic cancer underwent endoscopic variceal treatment as a rescue therapy but finally died of refractory gastrointestinal (GI) bleeding; another younger patient with chronic pancreatitis died of massive GI bleeding; and the remaining three patients survived at their last follow-up. Conclusions. LSPH should be seriously taken into consideration in patients with pancreatic diseases who develop upper GI bleeding. Clinicians should individualize the treatment strategy of LSPH according to the patients' clinical conditions and nature of pancreatic diseases.